Primary nasal tuberculosis during anti-tumour necrosis factor alpha treatment of a patient with rheumatoid arthritis. (December 2013) - Ribeiro, Sofia; Ferreira, Betânia; Duarte, Raquel; Almeida, Isabel; Vasconcelos, Carlos
Abstract Anti-tumour necrosis factor alpha (anti-TNFα) therapy is increasingly used in several inflammatory disease processes, including rheumatoid arthritis. However it has a significant potential for adverse events, such as reactivation of latent tuberculosis, which is frequently found in disseminated or extrapulmonary forms. We present a rare case of primary nasal tuberculosis within the context of anti-TNFα therapy for rheumatoid arthritis. To our knowledge, this is the first reported case of primary nasal tuberculosis in a patient with rheumatoid arthritis receiving anti-TNFα therapy.